Targeted Delivery of Tumor Suppressor microRNA-1 by Transferrin- Conjugated Lipopolyplex Nanoparticles to Patient-Derived Glioblastoma Stem Cells - Wang, Xinmei; Huang, Xiaomeng; Yang, Zhaogang; Gallego-Perez, Daniel; Ma, Junyu; Zhao, Xi; Xie, Jing; Nakano, Ichiro; Lee, L. J. (Current Pharmaceutical Biotechnology, 2014)
Objective: Among heterogeneous glioblastoma multiforme (GBM) cells, glioblastoma stem cells (GSCs) is a subpopulation having a critical role in tumor initiation and therapy resistance. Thus targeting GSCs would be an essential step to completely eradicate this lethal disease. MicroRNA-1 (miR-1) expression is deregulated in GBM patients and restoration of miR-1 by viral-vector in GBM cells has been demonstrated to inhibit tumor initiation and attenuate cell migration. Here, we show that a transferrin-targeting non-invasive nanoparticle delivery system (Tf-NP) can efficiently deliver miR-1 to GBM patient-derived GSC-enriched sphere cultures (GBM spheres). Methods: Delivery efficiency of the transferrin- targeting non-invasive nanoparticle was investigated by flow cytometry and further confirmed by confocal microscopy. The levels of miR-1 and its target molecules in GBM spheres were measured by qRT-PCR and immunoblotting. Migration capacity of Tf-NP-miR-1 treated GBM spheres were evaluated by transwell migration assay. Results: Tf-NPmiR- 1 treatment resulted in an over 200-fold increase of mature miR-1 compared to free miR-1 and Tf-NP-miR negative control (Tf-NP-miR-NC). Transferrin-mediated NP delivery resulted in a 3-fold higher delivery efficiency compared to NP without transferrin modification. Tf-NP-miR-1 treatment on GBM spheres significantly inhibited migration of GBM spheres by 30–50% with associated decline of MET and EGFR expression. Our data supported that Tf-NP could be used as an efficient and effective delivery system which has high potential to benefit the development of miR-based therapeutics for GBM treatment.
Keywords: cancer stem cells